Laws Relating to, and Ordinances of the Corporation of the Borough of Minersville, at 33, An Ordinance Prohibiting the Carrying of Concealed Weapons in the Borough of Minersville, and for other Purposes, § 1 (1887) - (:unkn) unknown (My University, 1858)
any person within the limits of said Borough of Minersville, who shall carry any fire arms, slung shot, or other deadly weapon concealed upon his person with the intent therewith unlawfully and willfully to injure any other person, shall be deemed guilty of a violation of this ordinance
Keywords: CARRY - CONCEALED